Targeting PI3Kγ/AKT Pathway Remodels LC3‐Associated Phagocytosis Induced Immunosuppression After Radiofrequency Ablation. Issue 7 (17th January 2022) - Liu, Xiaodi; Zhang, Wenyue; Xu, Yanni; Xu, Xiaolin; Jiang, Qiongchao; Ruan, Jingliang; Wu, Ye; Zhou, Yingshi; Saw, Phei Er; Luo, Baoming
Abstract: Residual tumors after insufficient radiofrequency ablation (IRFA) shows accelerated progression and anti‐PD‐1 resistance. It is also reported that macrophages infiltrating into residual tumors leads to anti‐PD‐1 resistance. Elements of autophagy have been detected to conjugate LC3 to be increasingly expressed in residual tumors. The underlying mechanisms between LC3 and macrophages are aimed to be investigated, and explore further ways to enhance immunotherapy in treating residual tumors. In mice models and patients, macrophages demonstrate increased infiltration into residual tumors, especially surrounding the ablated zone. Single‐cell transcriptome demonstrates enhancement of immunosuppression function in macrophages after IRFA. It is shown that macrophages engulf heat‐treated cells through LC3‐associated phagocytosis (LAP), enhance IL‐4 mediated macrophage programming through the PI3K γ /AKT pathway, and suppress T cell proliferation. Blockade of the PI3K γ /AKT pathway enhances the antitumor activity of PD‐1 blockades, inhibits malignant growth, and enhances survival in post‐IRFA models. In conclusion, in mice models and patients, macrophages demonstrate increased infiltration around ablated zones in residual tumors. Blockade of the PI3K γ /AKT pathway suppresses the growth of residual tumors in subcutaneous and orthotopic models. The results illustrate the translational potential of PI3K γ inhibitors to enhance anti‐PD‐1 therapy for the treatment of residual tumors after IRFA. Abstract : In hepatocellular carcinoma treated by insufficient radiofrequency ablation, LC3‐associated phagocytosis (LAP) is induced in macrophages, where the macrophages engulf dying tumor cells. Cholesterol efflux during LAP enhances IL‐4 mediated programming and activates the PI3K γ /AKT pathway. Cytokines including CCL7 and IL‐10 are produced after LAP. Simultaneously, inhibition of LAP and blockade of the PI3K γ /AKT pathway remodels the immunosuppressive state of macrophages.